Implementasi Kebijakan Kurikulum Merdeka Sekolah Menengah Kejuruan di Kota Serang (Studi Pada SMKN 3 Kota Serang) - SAEPUDIN, ELI (Yayasan Perguruan Kampus, 2024)
The successful implementation of the independent curriculum policy must be supported by good school leadership, teacher creativity, student activity, socialization of the Merdeka curriculum, learning facilities and resources, a conducive academic environment, and the participation of school residents. Factors Affecting Outside Policies in the Implementation of the Independent Curriculum Policy at SMK 3 Serang City School are Suggestions for socio-economic conditions The implementation of the independent curriculum policy at SMK 3 Serang City School must be supported by complete infrastructure. Not only relying on BOS alone for the successful implementation of the independent curriculum policy but there must be monitoring from the provincial government, the education office. This research uses descriptive qualitative methods with observation and interview methods.